Régimen municipal y gestión local: análisis de las capacidades de los gobiernos del conurbano bonaerense en el contexto de la pandemia de COVID-19 - Amaya, Paula (2021)
Three decades ago, following a constitutional reform, municipalities in Argentina went from being administrative delegations to enjoying full autonomy. With the passage of time, the lack of modernization at the local level and the arrival of the pandemic caused by COVID-19 have led to the emergence of new demands and social expectations. In this scenario, the analysis of the management and restructuring of municipal government priorities is of vital importance.  In this article, the authors analyze, on the basis of a field research carried out during the second semester of 2020 and the first semester of 2021, the management of four municipalities in the south of the Buenos Aires conurbation. To this end, they base their analysis, among other criteria, on the planning and evaluation of results; the design of organizational structures; and the definition of priorities, sectoral objectives and tasks in terms of public employment. In addition, they reflect on possible alternatives to improve the institutional capacity of these governments and question the structural limits that operate as a barrier to such improvement.